Female adolescents and the use of contraceptives in rural areas - Nuzzulil Nur Abdilla; Sutinah Sutinah (Jurnal Sosiologi Dialektika, 2021)
Contraception is an effort used to prevent pregnancy in women of childbearing age. Presently, contraception is not only used for adult women or those who have had a partner, but also for female adolescents. This study aimed to understand the practice of using contraceptives among female adolescents in rural areas. The theory used as an analytical tool was the theory of social construction by Peter L Berger and Thomas Luckmann. This study used a qualitative method. The research subjects in this study were women who used contraceptives as an adolescent. This study showed that the use of contraceptives or family planning by female adolescents in the Kabuh District is a common practice. Female adolescents interpreted family planning practices as prevention of pregnancy. The most commonly used contraceptives are the contraceptive injection and the birth control pill. Adolescents obtained preference for contraceptives from their parents and family. Meanwhile, family planning services were only provided through a midwife using the One-Stop Service method. Cultural values and customs that are deeply rooted in the Manduro community make the practice of pre-marital family planning perpetuated, even though it contradicts information in general and religion. This study concluded that the practice of pre-marital family planning is believed to be the best solution for female adolescents who are engaged but still want to seek new experiences.